Urgensi Penetapan Pas Lintas Batas Antara Pulau Atauro (Timor Leste) Dan Pulau Lirang (Indonesia) Dari Perspektif Hukum Keimigrasian - Yansen Paulus Rinaldy Andries; Arman Anwar (Faculty of Law, Universitas Pattimura, 2021)
Introduction: This study discusses the problem that has not been applied to the Cross-border Pass between the island of Atauro (Timor Leste) and the Island of Lirang (Indonesia) which has resulted in people from the two islands being able to freely enter and exit the border area without immigration checks. Indonesia.Purposes of the Research: Analyzing and knowing the urgency of establishing a cross-border pass between Atauro Island (Timor Leste) and Lirang Island (Indonesia) from the perspective of immigration law. Methods of the Research: This study uses a normative juridical method with the legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: The urgency of establishing a cross-border pass between the island of Atauro (Timor Leste) and Lirang Island (Indonesia) from the perspective of immigration law, namely: other laws, such as economic law, international law and criminal law. In connection with this, if there is no permission from each country for its citizens to cross the border area then this action is an illegal act or a violation in the field of immigration. Therefore, the determination of the Cross-Border Pass and the construction of the Cross-Border Post must immediately be carried out on Atauro Island (Timor Leste) and Lirang (Indonesia).